2013
DOI: 10.1016/j.ijppaw.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Networks and the ecology of parasite transmission: A framework for wildlife parasitology

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
130
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 123 publications
1
130
0
2
Order By: Relevance
“…Social network approaches are a common method in infectious disease ecology to document contact patterns among interacting individuals and for modelling the spread of pathogens [1][2][3][4][5][6]. In a network approach, the epidemiological units of infection (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social network approaches are a common method in infectious disease ecology to document contact patterns among interacting individuals and for modelling the spread of pathogens [1][2][3][4][5][6]. In a network approach, the epidemiological units of infection (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In a network approach, the epidemiological units of infection (e.g. individuals, herds, farms) are defined as nodes and inter-linked according to who is in contact with whom, where contact is assumed to represent transmission opportunities between the two nodes [2,3]. Theoretical work has repeatedly demonstrated that incorporating contact pattern heterogeneity into epidemiological models can substantially alter model predictions [6][7][8], while empirical studies show that network connectivity influences the risk of an individual acquiring an infection [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behaviours that facilitate direct and indirect transmission can be very different; the former requires spatial and temporal co-occurrence and often a specific behavioural interaction, while indirect transmission can simply require spatial co-occurrence within a certain time window (Godfrey, 2013). This distinction can be particularly important when direct interactions among potential hosts are rare, which is likely to be the case for between-species transmission (Viana et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the interest in understanding disease transmission among wild and domestic animals, and between them and human population has grown, resulting in the emergence of the "one health approach", which aims to model the transmission of parasitic diseases [7,8]. Detection and transmission control constitute significant components to the overall management of many pathogen infections (including parasites).…”
Section: Introductionmentioning
confidence: 99%